Efekt Portevina-Lechateliera w Próbie Ściskania Polikrystalicznego Aluminium - Klepaczko, J.; Malinowski, Z. (Engineering Transactions, 1973)
In the paper are presented the results of cxperiments concerning the Portevin-Le Chatelier effect (called the PL effect) and obtained as a result of compression tests of polycrystalline alumminum. The results reveal an essential dependence of the PL effect on the initial slenderness ratio of the specimen so=lo/do. Comparison of the existing experimental data yields the conclusion that the corse of the phenomenon in the process of compressive deformation of the specimen is different from that of the tension and torsion tests as presented in the literature. Basing on the theory of the effect, a detailed discussion of the influence of strain upon the magnitudes governing the PL effect is presented. Particular attention is paid to the state of hydrostatic pressure occuring in the specimen, assumption being made that the differences appearing in the effects observed in compression tests and in tension and torsion tests may result from the influence of the mean stress value on the diffusion processes and on the velocity of dislocation propagation. The analysis performed makes it possible to formulate a hypothetical interpretation of the experimental results presented in the paper and concerning the compression process, use being made of the information known from the literature effect observed in the tension and torsion tests. The physical interpretation of the PL effect in polycrystalline aluminum proposed in the paper enables us to explain not only its different character in compression tests, but also the experimentally determined relations where e is the critical strain at which the PL effect appears, and 8 denotes the strain rate.